2001
DOI: 10.1074/jbc.m104041200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CD151·α3β1 Integrin and CD151·Tetraspanin Interactions by Mutagenesis

Abstract: Transmembrane proteins of the tetraspanin superfamily are associated with various integrins and modulate their function. We performed mutagenesis analysis to establish structural requirements for the interaction of CD151 with the ␣ 3 ␤ 1 integrin and with other tetraspanins. Using a panel of CD151/CD9 chimeras and CD151 deletion mutants we show that the minimal region, which confers stable (e.g. Triton X-100-resistant) association of the tetraspanin with ␣ 3 ␤ 1 , maps within the large extracellular loop (LECL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 39 publications
6
82
0
Order By: Relevance
“…Our data now support a ''transmembrane linker'' model in which (i) the integrin contacts laminin, (ii) CD151 forms an extracellular contact with the ␣ subunit of laminin-binding integrins (31,35), and (iii) CD151 uses its short cytoplasmic tail to engage as yet unidentified membraneproximal elements. These unknown elements are critical for strengthening integrin-mediated adhesion, such that it withstands larger mechanical forces.…”
Section: Discussionsupporting
confidence: 66%
“…Our data now support a ''transmembrane linker'' model in which (i) the integrin contacts laminin, (ii) CD151 forms an extracellular contact with the ␣ subunit of laminin-binding integrins (31,35), and (iii) CD151 uses its short cytoplasmic tail to engage as yet unidentified membraneproximal elements. These unknown elements are critical for strengthening integrin-mediated adhesion, such that it withstands larger mechanical forces.…”
Section: Discussionsupporting
confidence: 66%
“…The best characterized tetraspanin/partner pair is CD151/integrin ␣3␤1, and several studies have revealed the importance of the CD151 large extracellular domain for this interaction (37,38). This is consistent with the LEL of tetraspanins being the most variable region of these molecules (14 -16).…”
Section: Discussionsupporting
confidence: 65%
“…Unlike tetraspanin, CLRN1 does not conserve the structurally essential cysteine residues in the second extracellular loop that tetraspanins dedicate to forming intramolecular disulfide-bonds. These disulfide bonds were found to be required for the heterophilic interaction of tetraspanin with its cognate integrin, as well as for the homophilic interaction between tetraspanins themselves (47). Although CLRN1 has no cysteine residues in the second extracellular loop, significant interactions between CLRN1 and integrin subunits still occur.…”
Section: Discussionmentioning
confidence: 99%